OPTIMISME DAN HARAPAN TERHADAP KINERJA PERAWAT MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT PONDOK INDAH - Pahniar Noviza; Agus Fauzi (Jurnal Satya Mandiri Manajemen dan Bisnis, 2022)
The purpose of this study was to determine the effect of optimism and hope on the performance of nurses through satisfaction at Pondok Indah Hospital. The research methodology is a survey with quantitative analysis techniques and path analysis applied in hypothesis testing. The study was conducted on 226 nurses as a simple random sample. The results of the analysis and interpretation of the data show that: (1) optimism has a direct and significant effect on job satisfaction, (2) expectations have a direct and significant effect on job satisfaction, (3) optimism has a direct and significant effect on nurse performance, (4) expectations have a direct effect on performance. nurses, (5) satisfaction has a direct effect on nurse performance, (6) optimism has an indirect effect on nurse performance and (7) hope has an indirect effect on nurse performance.